Bridging the gap: reply to discussion of "Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants". Issue 7 (19th May 2022) - Rangecroft, Sally; Rohse, Melanie; Banks, Eddie W.; Day, Rosie; Di Baldassarre, Giuliano; Frommen, Theresa; Hayashi, Yasunori; Höllermann, Britta; Lebek, Karen; Mondino, Elena; Rusca, Maria; Wens, Marthe; et al.
ABSTRACT: In this reply we thank both authors for their thoughtful insights on our original opinion piece "Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants." We believe these discussions will help to inspire and guide current and future researchers and illustrate how to continue to bring together physical and social data, experiences, and perspectives, and bridge the gap between the two disciplines with respect to socio-hydrological topics. Furthermore, we are confident that these insights and experiences will help foster a deeper understanding for hydrologists and natural scientists engaging with these discussions and research. Here we focus on two important themes that cut across both Quandt and Haeffner's replies: (1) further discussions on the importance of perceptions and lived experiences; and (2) further discussions on collaborative working and some of the major external barriers.